Strengthening Islamic Literacy Networks through Cross Border Organizational Da’wah: A Case Study of Sygma Daya Insani’s Annual Meeting SLC 2025 - Enik Fa’izah; Dewi Santi (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
The expansion of digital communication has transformed Islamic da'wah by widening access to religious knowledge while simultaneously raising questions about credibility, authority, and the sustainability of literacy practices. This study examines how Sygma Daya Insani's (SDI) Annual Meeting SLC 2025 functioned as a cross-border organizational space for strengthening Islamic literacy-based da'wah. Using a qualitative single-case study design, data were collected during activities held in Malaysia and Thailand from 3 to 7 May 2025 through semi-structured interviews, participant observation, field documentation, and public organizational documents. The data were analyzed iteratively through organization and condensation, initial coding, thematic development, cross-source comparison, triangulation, and interpretation. The findings show that the meeting operated not merely as an organizational event but as a temporary space for coordinating dispersed actors, circulating literacy resources, connecting face-to-face activities with digital communication, and reinforcing collective identity through recognition practices. These processes were synthesized into the Cross-Border Islamic Literacy Network framework, comprising four interconnected mechanisms: knowledge production, relational coordination, hybrid circulation, and symbolic recognition. The study contributes to discussions on digital religion and transregional Islam by shifting attention from individual religious actors and media platforms toward the organizational infrastructure supporting Islamic knowledge circulation. Practically, the findings highlight the importance of integrating credible literacy resources, interpersonal coordination, responsible digital communication, and meaningful recognition to sustain literacy-based da'wah. As a single bounded case, the findings are context-specific and require further examination across different organizations and cross-border settings